inverse expression



Sorry for the slow reply -- apparently there was a problem in some
mail system somewhere, and your message just arrived.

          -s

On Thu, Nov 18, 2010 at 12:51, Seb <spluque at gmail.com> wrote:
> =A * exp(-b * exp(-k * x))

(%i46) eq(x):=A * exp(-b * exp(-k * x))$
(%i47) solve(eq(x)=len,x);
(%o47) [x = log(b/log(A/len))/k]

You don't need to define a function -- you can work directly on the equation:

(%i48) eq: len = A * exp(-b * exp(-k * x))$
(%i49) solve(eq,x);
(%o49) [x = log(b/log(A/len))/k]